2021
DOI: 10.2196/22934
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence for Skin Cancer Detection: Scoping Review

Abstract: Background Skin cancer is the most common cancer type affecting humans. Traditional skin cancer diagnosis methods are costly, require a professional physician, and take time. Hence, to aid in diagnosing skin cancer, artificial intelligence (AI) tools are being used, including shallow and deep machine learning–based methodologies that are trained to detect and classify skin cancer using computer algorithms and deep neural networks. Objective The aim of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Model Performance AI models in this review showed reasonably highperformance classification using both dermoscopic and clinical images in populations with skin of color. Accuracy was greater than 70% for all binary models reviewed, which is similar to models developed using Caucasian datasets [46]. It has previously been suggested that instead of training algorithms on more diverse datasets, it may be beneficial to develop separate algorithms for different populations [7].…”
Section: Diversity and Transparencysupporting
confidence: 65%
“…Model Performance AI models in this review showed reasonably highperformance classification using both dermoscopic and clinical images in populations with skin of color. Accuracy was greater than 70% for all binary models reviewed, which is similar to models developed using Caucasian datasets [46]. It has previously been suggested that instead of training algorithms on more diverse datasets, it may be beneficial to develop separate algorithms for different populations [7].…”
Section: Diversity and Transparencysupporting
confidence: 65%
“…Third, we did not examine the benefits of the GEN product on facial skin at the molecular level. Further research into the advantages of the GEN product using cutting-edge molecular testing and/or some more recent technologies, such as artificial intelligence-based methods for assessing facial skin lesions and conditions, may be of interest [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Takkidin at al. [ 126 ] found that shallow models, most frequently, were built using a support vector machine (SVM) with maximum accuracy scores of 93–99% for the diagnosis of skin cancer, using relatively small data sets. On the other hand, in the case of deep models, convolutional neural networks (CNN) were the most commonly used method for skin cancer detection, with a maximum accuracy of 94–96% using medium-size data sets [ 126 ].…”
Section: Techniquesmentioning
confidence: 99%